Synthesis, Characterization and Spectroscopic Studies of a6, 6’-((1E, 1’E)-(1, 2-phenylene bis (azanylylidene)) bis (methanylylidene)) bis (3-(phenyldiazenyl) phenol) and their Complexes - Saher Al-Shamkhawy (Journal of Global Pharma Technology, 2018)
A new ligand 6, 6’-((1E, 1’E)-(1, 2-phenylenebis (azanylylidene)) bis (methanylylidene)) bis(3-(phenyldiazenyl)phenol) (L2) was prepared and characterized by UV-visible, FT-IR, 1H-NMR and Mass spectra. Two complexes with Cu (II) and Co (II) ions were prepared. The preparation has demeanor after limitation the optimum conditions through (UV-Vis) spectrophotometric study of these complex solutions have been studied such as determination wavelength (λmax), volume reagent, effect of time, effect of temperature and effect of pH .Also study determination of dissociation degree and stability constant under wavelength (λmax) and optimum pH values. The structures of complexes are Evidenced approbate to job method which were gained from the spectroscopic studies of the complex solutions and characterized by molar conductance measurements, infrared spectra and mass spectra at room temperature. The infrared spectra of the chelating complexes have been studied, this may suggest that coordination between the metal ions and the prepared ligand takes place. The analytical data show that the metal to ligand ratio [M: L] in two complexes is (1:1) (metal: ligand) stoichiometry. depending on these results, the ligand acts as a bidentate ligand coordination through –C=N and –OH groups, the proposed geometrical structures of the complexes of Cu(II) and Co(II) ions are octahedral.Keywords: Azo-azomethine, Metal complexes, Synthesis, Spectral Studies.